Comparison of five lists to identify potentially inappropriate use of non-steroidal anti-inflammatory drugs in older adults - Nguyen, Thi Ngoc Mai; Laetsch, Dana Clarissa; Chen, Li-Ju; Holleczek, Bernd; Meid, Andreas; Brenner, Hermann; Schöttker, Ben (Pain medicine, 2021)
To compare the prevalence of potentially inappropriate non-steroidal anti-inflammatory drugs (NSAIDs) among NSAIDs users defined with frequently used potentially inappropriate medication (PIM) lists and to identify the determinants of their use.Cross-sectional survey among community-dwelling older adults from Germany.N = 284 NSAIDs users aged 65-89 years.All currently regularly or as-needed used drugs were recorded during a home visit. Multivariate logistic regression models were applied to assess the potential determinants of potentially inappropriate NSAIDs use.Prevalence of potentially inappropriate NSAIDs use was 54.2%, 45.4%, 29.9%, 20.4%, and 3.5% when applying the STOPP, 2019 Beers, EU(7)-PIM, FORTA, and PRISCUS list, respectively. No study participant was identified as a potentially inappropriate NSAIDs user by all five lists simultaneously. The majority (68%) were identified only by one or two lists. Merely the STOPP and Beers criteria had a moderate inter-instrument agreement. Lower pain severity, gout, peptic ulcer (PU), cardiovascular disease (CVD), and chronic kidney disease (CKD) were statistically significantly associated with potentially inappropriate NSAIDs use defined by the STOPP criteria and the latter three conditions also with the 2019 Beers criteria.The STOPP and Beers criteria may be superior to the other lists because they more frequently identify potentially inappropriate NSAIDs use in conditions implying a high risk for NSAIDs' adverse events (i.e., PUD, CKD and CVD). We developed a harmonized, country-independent PIM list for NSAIDs with the same advantages as observed for the STOOP and 2019 Beers criteria and recommended its use.
Gesehen am 04.11.2021